Value management in infrastructure projects in Western Australia: techniques and staging - Whyte, Andrew; Cammarano, Carlo (ARCOM, Association of Researchers in Construction Management, 2012)
Infrastructure projects to service the mining industry in Western Australia (WA) are on the increase, somewhat in contrast to a stalling of projects nationally and globally. It remains important therefore for WA companies to be competitive in the realisation of a client's brief. Value management (VM) has long been regarded as an effective means to eliminate unnecessary capital and life-cycle costs, however, whilst many are familiar with the underlying theory, its use locally is perceived to be less widespread. The research presented here investigates the extent to which value management is implemented by Western Australian engineering and construction companies in both the design and construction fields; exploring, the various value management techniques used in practice and, VM staging. This study documents benefits achieved by means of value management and, the attitudes of industry professionals towards the feasibility or need in establishing a compulsory value management procedure for all (civil engineering) developments. To investigate current value management implementation in WA a pilot-study research methodology embraced a qualitative semi-structured interview approach of ten respondents from organisations involved in design and construction of civil engineering work. Straw poll project results suggest WA industry to be well aware of both, the concept of value management and, the benefits that may arise from its use to address the life-cycle of a project; case-study specification analysis is then presented to explore VM benefits/disbenefits explicitly.The research presented here concludes that industry does have formal value management procedures within a preliminary design phase. Findings show however that industry is resistant to a statutory requirement for value management and, argue that in WA competition is enough to drive the uptake and utilisation of VM.